Paraventricular oxytocin neurons impact energy intake and expenditure: projections to the bed nucleus of the stria terminalis reduce sucrose consumption - Worth, Amy A.; Feetham, Claire H.; Morrissey, Nicole A.; Luckman, Simon M. (Frontiers in Endocrinology, 2024)
The part played by oxytocin and oxytocin neurons in the regulation of food intake is controversial. There is much pharmacological data to support a role for oxytocin notably in regulating sugar consumption, however, several recent experiments have questioned the importance of oxytocin neurons themselves.Methods: Here we use a combination of histological and chemogenetic techniques to investigate the selective activation or inhibition of oxytocin neurons in the hypothalamic paraventricular nucleus (Oxt PVH ). We then identify a pathway from Oxt PVH neurons to the bed nucleus of the stria terminalis using the cell-selective expression of channel rhodopsin.Oxt PVH neurons increase their expression of cFos after both physiological (fast-induced refeeding or oral lipid) and pharmacological (systemic administration of cholecystokinin or lithium chloride) anorectic signals. Chemogenetic activation of Oxt PVH neurons is sufficient to decrease freefeeding in Oxt Cre:hM3Dq mice, while inhibition in Oxt Cre:hM4Di mice attenuates the response to administration of cholecystokinin. Activation of Oxt PVH neurons also increases energy expenditure and core-body temperature, without a significant effect on locomotor activity. Finally, the selective, optogenetic stimulation of a pathway from Oxt PVH neurons to the bed nucleus of the stria terminalis reduces the consumption of sucrose.Our results support a role for oxytocin neurons in the regulation of whole-body metabolism, including a modulatory action on food intake and energy expenditure. Furthermore, we demonstrate that the pathway from Oxt PVH neurons to the bed nucleus of the stria terminalis can regulate sugar consumption.